Collapsin Response Mediator Proteins: Their Biological Functions and Pathophysiology in Neuronal Development and Regeneration - Nakamura, Fumio; Ohshima, Toshio; Goshima, Yoshio (Frontiers in Cellular Neuroscience, 2020)
Collapsin response mediator proteins (CRMPs), which consist of five homologous cytosolic proteins, are one of the major phosphoproteins in the developing nervous system. The prominent feature of the CRMP family proteins is a new class of microtubule-associated proteins that play important roles in the whole process of developing the nervous system, such as axon guidance, synapse maturation, cell migration, and even in adult brain function. The CRMP C-terminal region is subjected to posttranslational modifications such as phosphorylation, which, in turn, regulates the interaction between the CRMPs and various kinds of proteins including receptors, ion channels, cytoskeletal proteins, and motor proteins. The gene-knockout of the CRMP family proteins produces different phenotypes, thereby showing distinct roles of all CRMP family proteins. Also, the phenotypic analysis of a non-phosphorylated form of CRMP2-knockin mouse model, and studies of pharmacological responses to CRMP-related drugs suggest that the phosphorylation/dephosphorylation process plays a pivotal role in pathophysiology in neuronal development, regeneration, and neurodegenerative disorders, thus showing CRMPs as promising target molecules for therapeutic intervention.